Food trucks consumers in Salvador – Bahia: Profile, food practices and perceptions (Research, Society and Development, 2022)
Food trucks (FT) are an innovation in the street food segment. In Brazil, this sector started its activities in 2013, arriving in Salvador, Bahia, in 2015. In the city, FTs are present, above all, in gastronomic events, attracting many people. Given this phenomenon, this study aimed to characterize FT consumers, considering their profile, practices, and perceptions in Salvador, Bahia state. An exploratory, quantitative study was carried out, with the application of a semi-structured questionnaire, along with 128 consumers of FT. A balanced distribution between men (50.78%) and women (49.22%) was observed, predominantly young adults (80.47%), single (76.56%), with complete or incomplete higher education (58.89%), and average family income corresponding to classes C and D (77.34%). The most cited reasons for consumption in FT were practicality (54.69%), taste and/or pleasure (43.75%), and price (10.94%). Many consumers (54.69%) had been using FTs for more than a year, although infrequently (44.53%). For the interviewees, the hygiene of the FTs was considered good (82.03%) and the food quality was reliable (74.22%). Among the sale points’ selection criteria were highlighted:  the appearance of the preparations (68.75%) and the seller (64.84%), the cleanliness of the place (50.78%), the packaging of the products (35 .59%), and the price (32.81%). Most consumers (95.31%) believed in the continuity of the FT service, emphasizing reasons such as the practicality, affordable price, and diversity of preparations. The study shows that FT consumers have a different profile - young people, with higher education and income, who seek gastronomic experiences, new forms of leisure and social interactions. Thus, they are distinct from the traditional street food collective.